2017
DOI: 10.1051/0004-6361/201629140
|View full text |Cite
|
Sign up to set email alerts
|

Condensation-inhibited convection in hydrogen-rich atmospheres

Abstract: In an atmosphere, a cloud condensation region is characterized by a strong vertical gradient in the abundance of the related condensing species. On Earth, the ensuing gradient of mean molecular weight has relatively few dynamical consequences because N 2 is heavier than water vapor, so that only the release of latent heat significantly impacts convection. On the contrary, in an hydrogen dominated atmosphere (e.g. giant planets), all condensing species are significantly heavier than the background gas. This can… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
127
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 49 publications
4
127
2
Order By: Relevance
“…Using the thermal evolution calculations, Lupu et al (2016) estimated the internal heat fluxes for known widely separated giant planets, and found that very massive planets such as Ups And d could have high effective temperatures dominated by the internal heat flows. We additionally note that the internal heat flux predicted by thermal evolution models should probably be adopted as an upper limit, because there are mechanisms to temporarily inhibit vertical heat transport in giant planets (e.g., Leconte et al 2017), and because empirically, the cause for Uranus's particularly low internal heat flux is still poorly understood (e.g., Fortney & Nettelmann 2010). Figure 3 shows the cloud top pressure, defined as the pressure at which the vertical optical depth of cloud particles equals unity, as a function of the atmospheric metallicity.…”
Section: Cloud Type and Pressure Levelmentioning
confidence: 99%
“…Using the thermal evolution calculations, Lupu et al (2016) estimated the internal heat fluxes for known widely separated giant planets, and found that very massive planets such as Ups And d could have high effective temperatures dominated by the internal heat flows. We additionally note that the internal heat flux predicted by thermal evolution models should probably be adopted as an upper limit, because there are mechanisms to temporarily inhibit vertical heat transport in giant planets (e.g., Leconte et al 2017), and because empirically, the cause for Uranus's particularly low internal heat flux is still poorly understood (e.g., Fortney & Nettelmann 2010). Figure 3 shows the cloud top pressure, defined as the pressure at which the vertical optical depth of cloud particles equals unity, as a function of the atmospheric metallicity.…”
Section: Cloud Type and Pressure Levelmentioning
confidence: 99%
“…Even with moist convection, there would still be the question of how the internal heat gets from 40–60 bars to the base of the water cloud. A radiative zone near the water cloud base is a possibility, but it requires a water abundance that is more than 10 times the solar value, and that seems unlikely [ Leconte et al ., ]. A radiative zone could exist between the 1200 and 2900 K levels, but it is not likely to extend into the range covered in Figure [ Guillot et al ., ].…”
Section: Belts and Zonesmentioning
confidence: 99%
“…The high abundance of methane is shown to inhibit convection in its cloud formation region (between 1 and 2 bar) and leads to a superadiabatic temperature gradient that was observed in Voyager radio-occultation data (Guillot 1995). If water is more than ten times solar, a similar but quantitatively stronger effect may occur, characterized by the presence of a deep radiative zone with a strong increase of the temperature with depth (Guillot 1995;Leconte et al 2017). Still deeper, diffusive convection should occur in regions with compositional changes, also leading to a superadiabatic temperature gradient (e.g., Rosenblum et al 2011).…”
Section: Uranus and Neptunementioning
confidence: 88%